Policies for a sustainable biomass energy sector in Malawi: Enhancing energy and food security simultaneously - Schuenemann, Franziska; Msangi, Siwa; Zeller, Manfred (Elsevier, 2018)
Biomass energy still dominates the energy sector in Sub-Saharan Africa, in particular as the main cooking energy source in rural and urban areas. The strong linkages to food security and the environment place biomass energy at the heart of sustainable development, a fact that is largely ignored by policy makers in favor of modern energy. At the same time, population and GDP growth are exacerbating already existing supply–demand imbalances in highly populated countries such as Malawi. These trends make it imperative to identify policy interventions that promote sustainable biomass energy while simultaneously considering linkages with other sectors. We use new data on demand and supply for biomass energy in Malawi and develop a model that estimates fuelwood demand based on actual diets and project demand in future years. We simulate how demand side interventions in the form of improved cookstoves affect biomass demand and built a behavioral model to analyze the potential of agroforestry for promoting a sustainable biomass energy sector in Malawi. Our findings show that policy measures aimed at increasing cooking efficiency are not enough to decrease demand for cooking energy due to high population growth. Supply side interventions like agroforestry on the other hand will not only increase sustainable supply, but can also enhance food security and protect the environment. We find that biomass energy can be inherently sustainable and should be an integral part of every energy sector strategy in developing countries as well as of the Sustainable Development Goals.